PEMBELAJARAN BAHASA ARAB UNTUK TUJUAN KHUSUS - Mohammad Arif Setyabudi; Syamsuddin; Hanifuddin (Program Studi Pendidikan Bahasa Arab, 2020)
Arabic is one of the most widely spoken languages in the world. Most of the world'spopulation, in the Arabian peninsula and in Muslim countries use Arabic not only as alanguage for worship, but also as a language of communication, both spoken andwritten. In learning Arabic, there are two main objectives, namely learning Arabic forlife and learning Arabic for special purposes. Arabic learning for special purposes isprepared for learners who want to master the language functionally and practically, in arelatively limited scope. In the Arabic language learning program for special purposes,the learning materials and curriculum are arranged specifically and systematically bytaking into account the diversity of backgrounds and the needs of learners. In learning, itis not tied to certain methods, but takes into account the interests and motivations of thelearners.